Foreign Currency Translation and Changing Prices in Perfect and Complete Markets - Beaver, William H.; Wolfson, Mark A. (Journal of Accounting Research, 1982)
William H. Beaver, Mark A. Wolfson, Foreign Currency Translation and Changing Prices in Perfect and Complete Markets, Journal of Accounting Research, Vol. 20, No. 2, Part II (Autumn, 1982), pp. 528-550